Cold ion demagnetization near the X‐line of magnetic reconnection. Issue 13 (13th July 2016) - Toledo‐Redondo, Sergio; André, Mats; Khotyaintsev, Yuri V.; Vaivads, Andris; Walsh, Andrew; Li, Wenya; Graham, Daniel B.; Lavraud, Benoit; Masson, Arnaud; Aunai, Nicolas; Divin, Andrey; Dargent, Jeremy; et al.
Abstract: Although the effects of magnetic reconnection in magnetospheres can be observed at planetary scales, reconnection is initiated at electron scales in a plasma. Surrounding the electron diffusion region, there is an Ion‐Decoupling Region (IDR) of the size of the ion length scales (inertial length and gyroradius). Reconnection at the Earth's magnetopause often includes cold magnetospheric (few tens of eV), hot magnetospheric (10 keV), and magnetosheath (1 keV) ions, with different gyroradius length scales. We report observations of a subregion inside the IDR of the size of the cold ion population gyroradius (∼15 km) where the cold ions are demagnetized and accelerated parallel to the Hall electric field. Outside the subregion, cold ions follow theE ×B motion together with electrons, while hot ions are demagnetized. We observe a sharp cold ion density gradient separating the two regions, which we identify as the cold and hot IDRs. Key Points: High‐resolution observations of cold ions near the X‐line Cold ions decouple from hot ions inside the separatrices and follow the electron motion A layer at cold ion scales (cold IDR) is found near the X‐line where cold ions are demagnetized and accelerated parallel to E